Blood‐based biomarkers for Alzheimer's pathology and the diagnostic process for a disease‐modifying treatment: Projecting the impact on the cost and wait times. Issue 1 (18th August 2020) - Mattke, Soeren; Cho, Sang Kyu; Bittner, Tobias; Hlávka, Jakub; Hanson, Mark
Abstract: Introduction: Concerns have been raised about the limited health system capacity for identification of patients who are eligible for a disease‐modifying Alzheimer's treatment (DMT). Blood‐based biomarker (BBBM) tests are a promising tool to improve triaging at the primary care level. We projected their impact on cost of and wait times during the diagnostic process. Methods: We compare four scenarios for triaging patients at the primary care level from the perspective of the U.S. health care system: (1) cognitive test only (Mini Mental State Examination [MMSE]), (2) BBBM test only, (3) MMSE followed by BBBM if positive, and (4) BBBM followed by MMSE if positive. Results: Referring patients to dementa specialists based on MMSE or BBBM results alone would continuously require more specialist appointments than projected to be available until 2050. Combining MMSE and BBBM would eliminate wait lists after the first 3 years and reduce average annual cost by 400 to 700 million, while increasing correctly identified cases by about 120, 000 per year. Discussion: The combination BBBM with MMSE is projected to increase the efficiency and value of the triage process for DMT eligibility.